Age-dependent relationship between the carotid intima-media thickness, baroreflex sensitivity, and the inter-beat interval in normotensive and hypertensive subjects - Lábrová, R; Honzíková, N; Maderová, E; Vysocanová, P; Nováková, Z; Závodná, E; Fiser, B; Semrád, B (Physiological research, 2005)
The interrelationship between baroreflex sensitivity expressed in ms/mm Hg (BRS) or in Hz/mm Hg (BRSf), carotid wall thickness (IMT), and age was investigated in hypertensive and normotensive subjects with respect to the mean inter-beat interval (IBI) and blood pressure (BP). BP monitoring was performed in 25 treated hypertensives (Hy; 47.4+/-9.2 years of age) and 23 normotensives (Norm; 44.5+/-8.1 years). IMT was measured by ultrasonography. BRS and BRSf were determined by the spectral method (five-minute non-invasive beat-to-beat recording of BP and IBI, Finapres, controlled breathing at a frequency of 0.33 Hz). Significant differences between Hy and Norm were detected in IMT (Hy: 0.624+/-0.183, Norm: 0.522+/-0.070 mm; p<0.01), BRS (Hy: 3.5+/-1.6, Norm: 5.7+/-2.3 ms/mm Hg; p<0.01), BRSf (Hy: 0.005+/-0.002, Norm: 0.009+/-0.004 Hz/mm Hg; p<0.01), systolic BP (Hy: 131+/-21, Norm: 116+/-17 mm Hg; p<0.01) and diastolic BP (Hy: 77+/-16, Norm: 64+/-12 mm Hg; p<0.01). A significant correlation was found between age and IMT (Norm: 0.523, p<0.05; Hy+Norm: 0.419, p<0.01), age and BRS (Norm: -0.596, p< 0.01; Hy+Norm: -0.496, p<0.01), age and BRSf (Norm: -0.555, p<0.01; Hy: -0.540, p <0.01; Hy+Norm: -0.627, p<0.01), age and IBI (Hy: 0.478, p<0.05), age and diastolic BP (Hy: -0.454, p<0.05), BRS and IMT (Hy+Norm: -0.327, p<0.05) and BRSf and IMT (Hy+Norm: -0.358, p<0.05). Hypertensive patients have increased IMT and decreased BRS and BRSf. The positive correlation between age and IMT and the negative correlation between age and BRS and BRSf are in agreement with the hypothesis that the age-dependent decrease of baroreflex sensitivity corresponds to the age-related structural changes of the carotid wall. Using two indices of baroreflex sensitivity, BRS and BRSf, we could show that baroreflex sensitivity in hypertensives is lower not only due to thickening of the carotid wall, but also due to aging.
Keywords: Tunica Intima; Humans; lidé středního věku; Tunica Media; Hypertension; Female; tunica intima; dospělí; Heart Rate; věkové faktory; lidé; baroreflex; Baroreflex; Adult; Carotid Arteries; ženské pohlaví; krevní tlak; Male; srdeční frekvence; Middle Aged; hypertenze; Age Factors; mužské pohlaví; Blood Pressure; arteriae carotides; tunica media